1995
DOI: 10.1017/s0022215100131706
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment in association with distal renal tubular acidosis among Saudi children

Abstract: A follow-up of seven patients with the autosomal recessive inherited syndrome of distal renal tubular acidosis (RTA) and sensorineural hearing loss is described. Five patients were diagnosed as having primary distal renal tubular acidosis and rickets, four were found to have severe sensorineural hearing loss of over 80 dB: two of which are brothers. Two patients were diagnosed as having secondary distal renal acidosis due to a genetic disorder called osteopetrosis; they are brothers and their audiograms showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This proposed mechanism can explain the clinical observation that systemic alkali therapy, although correcting systemic pH, fails to prevent progressive hearing loss in dRTA patients 9,10 . We speculate that the failure of this treatment to address the abnormal endolymphatic physiology accounts for the progressive hearing loss.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This proposed mechanism can explain the clinical observation that systemic alkali therapy, although correcting systemic pH, fails to prevent progressive hearing loss in dRTA patients 9,10 . We speculate that the failure of this treatment to address the abnormal endolymphatic physiology accounts for the progressive hearing loss.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a substantial fraction of these patients have progressive bilateral sensorineural hearing loss 5-10 (SNHL). Simple alkali replacement can correct the systemic metabolic defects, but such treatment does not appear to ameliorate or prevent progression of hearing loss 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Sustained correction of the acidosis may have had a protective effect on the development and progression of deafness in this patient. Although it has been suggested that alkali treatment does not prevent the progression of hearing impairment [12], the late development of hearing loss in some patients with distal RTA linked to ATP6V0A4 mutations might be related with inappropriate sustained control of acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…The association of dRTA and hearing loss (HL) was first noted in 1967 [2], and since that time several patients with this clinical condition have been reported [3,4]. Recently, the identification of the causative genes for dRTA has provided considerable progress in understanding the pathophysiology of this group of disorders [1].…”
Section: Introductionmentioning
confidence: 99%